An Analysis of Islamic Business Ethics in E-Wallet in Indonesia with A Case Study of Go-Pay - Minarni; Nur Asnawi (Journal of Islamic Economics Lariba, 2022)
This article aims to examine the E-wallet business from the perspective of Islamic Business Ethics. The reality in E-wallet transactions still raises pros and cons in terms of its validity according to the Islamic framework. This study uses a qualitative descriptive method and a phenomenological approach. The tendency of people in the industrial era 4.0 to use digital-based application services requires proper literacy for short and long term goals. The results of this study indicate that various types of E-wallet applications, one of which is Go-Pay, allegedly still contain things that are contrary to Islamic Business Ethics. This can be seen, among other things, in the provision of special discounts or free shipping for Go-Pay application users, as well as the deposition of user balances in conventional banks (ribawi banks). Contemporary scholars who argue that this transaction is permissible argue because the transaction uses a wadi'ah contract and is in the framework of paying ujrah in advance. Whereas the scholars who forbid the transaction argue that the transaction contract is qardh (debt receivable) so that if it brings out benefits in it then it is included in usury. In implementing Islamic business ethics in e-wallet cases, e-wallet users must pay attention to the validity of the contract according to Islam and the purpose of the transaction according to maslahah. As for e-wallet suppliers, they must prioritize aspects of transaction legitimacy, product halalness, honesty, responsibility and trustworthiness.